Analysis of Mustahik Welfare Effect in Bandar Lampung City through Zakat Policy and Zakat Administration - Indah Hermiati; Budi Puspo Priyadi; Sundarso Sundarso (Institut Ilmu Sosial dan Manajemen STIAMI, 2020)
Poverty can cause economic inequality if it is not handled appropriately in Islam poverty is near to kufr. One strategic role as an instrument to reduce poverty and disagreement in Islam is through zakat. The research objective is to study the zakat policy and zakat administration on mustahik welfare in Bandar Lampung City. Methods of this study using a quantitative method with multiple linear regression analysis techniques. The number of research samples were 37 respondents. Based on the results of research simultaneously shows that the zakat policy and zakat administration determine the significance of welfare while partial shows the zakat policy does not significantly oppose the administration of zakat significant on welfare.